Evaluation of growth traits, feed conversion efficiency and mortality pattern of different crosses of White Nicobari under intensive and back yard system - Chaterjee, R N; Rai, R B; Yadav, S P; Sunder, Jai; Senani, S; Kundu, A (The Indian Journal of Animal Sciences, 2005)
Birds of direct and reciprocal crosses of White Nicobari with ILI-80 maintained under intensive management (994) and under back yard management (278) system were evaluated for their growth traits, feed consumption, feed conversion efficiency and rate of mortality in different age groups. Pooled body weight (under intensive management) at second and fourth week of age differed significantly (P&lt0.05) among the progeny of direct and reciprocal crosses. Body weight of males and females of the progeny of direct cross differed significantly (P&lt0.05) at eighth week of age and onwards. The body, weight of males and females of the progenyof reciprocal cross (ILI-80 male * White Nicobari female) at and beyondfourth week of age differed significantly (P&lt0.05) under intensive management system. Under back yard management system, the pooled body weight of the progeny of direct and reciprocal crosses at eighth and twelfth week of age differed signiticantly (P&lt0.05). the male and female body weight of the progeny of direct cross under back yard differed significantly at eighth week of age, while, the same differed significantly (P&lt0.05) at eighth, tenth, twelfth and fourteenth week of age for the progeny of reciprocal cross. However, the male body weights were higher than female body weights. The average daily feed consumption (under intensive management system) varied from 16.11 to 56.88 g/day for direct cross and born 15.16 to 58.60 g/ day for reciprocal cross between first and twelfth week of age. Feed conversion efriciency for the progeny of both the crosses was best in third week and lowest in tenth week of age. Rate of mortality was higher among the progeny of both the crosses between 5-8 weeks and 9-12 weeks ofage due to natural outbreak of IBD under both the management systems. The mortality was higher for the progeny of direct cross under backyard system, while, the situation is just reverse For reciprocal cross. The cause of mortality were IBD, debility, enteritis, vitamin deficiency. liver infection etc, under intensive management system.